“Pyknodysostosis” A Case Report - Sapkota, Karna K; Gupta, Veena; Shrivastav, CP (Journal of Nepal Paediatric Society, 2009)
Pyknodysostosis is a rare disorder of skeletal dysplasia that is inherited as an autosomal recessive genetic trait. Several mutations have been found in the gene encoding cathepsin K - a lysosomal cysteine protease and the gene situated at 1q21. A mutation in this gene leads to loss of enzyme for osteoclastic activities responsible for the metabolism of skeletal system leading to defective bone remodeling and resorption and various other skeletal abnormalities. Here we report a case of 12 year old female from mid-western hilly region of Nepal with Pyknodysostosis having fracture femur and other skeletal dysplasia. The characteristic features of this syndrome are dwarfism, large open fontenelles, wide cranial sutures, small retrograde mandible, multiple fractures and osteosclerosis, dental abnormalities, short and broad hands and feet, blue sclera, multiple fractures and nail may be dysplastic. Key words: Pyknodysostosis, dysplasia, short stature doi: 10.3126/jnps.v29i2.2049 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.101-103